Distribution of zopiclone and main metabolites in hair following a single dose. (January 2020) - Hansen, Stine Lund; Johansen, Sys Stybe; Nielsen, Marie Katrine Klose; Nilsson, Gunnel; Kronstrand, Robert
Highlights: Controlled single-dose study of zopiclone in hair was performed on 16 volunteers. Four sampling time points after zopiclone intake studied by 5-mm hair segments. Reference levels for zopiclone and N -desmethylzopiclone in hair were established. No wash-out effect was detected within 4 months after a single dose of zopiclone. Hair sampling 1–2 months after a single intake of zopiclone is optimal. Abstract: In forensic investigations, such as drug-facilitated crimes, reference values are useful for interpretation of hair results. The aim of this study was to establish levels of zopiclone and two main metabolites, N -desmethylzopiclone and zopiclone N- oxide, in hair after the administration of a single dose of zopiclone, as very limited data are published. A controlled study was performed, where 16 volunteers consumed either 5 or 10 mg zopiclone. Hair was sampled prior to consumption and 14, 30, 60, and 120 days after intake. The deposition of drug in hair segments of all sampling time points was followed in small hair segments of 5-mm, using a validated ultra-high performance liquid chromatography–tandem mass spectrometry method. In all participants, hair segments corresponding to the time of intake were positive for zopiclone, but also with lower concentrations in the neighbouring segments. The highest zopiclone concentrations were detected in samples collected 30 or 60 days after intake. For all sampling time points maximum values for the 5-mg dose ranged from 5.0–370 pg/mg for zopiclone and 5.4 to 300 pg/mg for N- desmethylzopiclone, where the maximum values for the 10-mg dose ranged from 17 to 590 pg/mg for zopiclone and 25–410 pg/mg for N- desmethylzopiclone for all sampling time points. No significant difference in concentrations was found between the two dosing groups for either zopiclone or N- desmethylzopiclone. Almost half of the participants showed lower levels 14 days after intake than in the later sampling time points. The metabolite to parent drug ratio of N -desmethylzopiclone to zopiclone varied from 0.6 to 3.4 (median = 1.2) for the maximum levels of all sampling time points. N -desmethylzopiclone are suggested to serve as an additional marker to confirm the intake of zopiclone. Traces of zopiclone N -oxide were detected in hair from only eight participants. This study showed, that it was possible to follow zopiclone and N- desmethylzopiclone in hair for 4 months even though the drugs was divided into several segments in the latest collected hair samples, and no obvious wash-out effect between the sampling time points by e.g. personal hygiene could be discerned because the cumulated amount at each sampling time point was similar. We conclude that the analysis of short segments e.g. segments of 5-mm can help determine the time of a single intake of zopiclone and that obtaining a sample 1–2 months after a drug exposure provide the best conditions to detect and interpret the results.